China–United States Research Collaborations in Antimicrobial Resistance. (13th November 2018) - van Duin, David; Gu, Peidi; Dong, Jane; Paff, Melanie; Arias, Rebekka M; Evans, Beth; Yu, Yunsong; Li, Lanjuan; Zhang, Fujie; Liu, Zhengyin; Cao, Bin; Fowler, Vance G; et al.
Abstract: A strong synergy can result from China–US antimicrobial resistance (AMR) collaborations given similarities and differences between their respective healthcare systems and research infrastructures. The Antibacterial Resistance Leadership Group has employed a model of realistic growth, starting with a feasible, relatively low-resource observational study in a critical priority pathogen. This and other observational studies will provide vital scientific information required for the rational design of future interventional trials. In addition, it provides a mutual, low-risk opportunity for determining the strengths and opportunities of the research collaboration. Issues identified during the observational studies can be addressed prior to the initiation of high-resource interventional studies. Collaborative clinical AMR studies between China and the United States have tremendous potential to decrease AMR rates, improve responsible antibiotic use, and ultimately improve the lives of patients in both countries.